LANGUAGE IS A MEANS OF COMMUNICATION (Archive of Conferences, 2021)
Senior Lect In the Muslim world, religious beliefs played an important role in the emergence of a number of philological sciences, and it was the factor of religion, in particular, the scientific value of the Arabic language, based on the objective requirement of a clear and accurate understanding of the Qur'an and its content. Along with the understanding of the language of the Qur'an, there was a need to know and understand the grammatical, semantic and stylistic features of the Arabic language. Therefore, the study of its language on the basis of the text of the Qur'an as an example of the Arabic language of the VII century, in particular, the linguistic laws of the language, in particular,urer, PhD Theoretical ideas on the refinement of meaning, how they are expressed in the classification of the sciences of language, are necessary from the point of view of modern, historical linguistics, as well as from the point of view of defining the peculiarities of linguistic ideas in the Islamic world.